Pengaruh Model Pembelajaran Literasi, Orientasi, Kolaborasi, dan Refleksi Terhadap Keterampilan Literasi Sosial Budaya dan Pemahaman Moderasi Beragama Siswa - Rofidah Tamami; Harmanto Harmanto; Nuansa Bayu Segara (Fakultas Agama Islam Universitas Billfath, 2024)
This research aims to see the effect of the LOK-R (Literasi, Orientasi, Kolaborasi, dan Refleksi) learning model on improving students' socio-cultural literacy skills and understanding of religious moderation in social science learning. This research is quasi-experimental with a pretest-posttest control group design. The research population was students at MTs Putra Putri Simo, Lamongan. The research sample consisted of 8th grade students, consisting of 60 students, with 30 people in the experimental class and 30 people in the control class. The research instrument is in the form of pretest questions, which are carried out before implementing the LOK-R learning model to measure initial socio-cultural literacy skills and initial understanding of religious moderation in students. The results of the research and hypothesis testing show that: (1) there has been a significant increase in students' socio-cultural literacy skills using the LOK-R learning model; (2) there has been a significant increase in students' understanding of religious moderation using the LOK-R learning model; and (3) there are differences in socio-cultural literacy skills and understanding of religious moderation simultaneously between students who take part in learning using the LOK-R learning model and students who take part in learning using the guided inquiry learning model. So it is concluded that there is an influence of using the LOK-R learning model has an influence on improving socio-cultural literacy skills and understanding of religious moderation among students in social studies learning at MTs Putra Putri Simo, Lamongan.